2016
DOI: 10.1210/jc.2015-2948
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Base Pair in Frame Germline Deletion in Exon 7 Of RET Leads to Increased RET Phosphorylation, ERK Activation, and MEN2A

Abstract: The finding of bilateral pheochromocytoma and MTC in our patient was highly suspicious of a RET mutation. Exome sequencing revealed a 6-base-pair deletion in exon 7 of RET, an exon not yet associated with MEN2. Increased ligand-independent phosphorylation of the p.505_506del RET mutant, increased activation of downstream pathways, and stimulation of cell proliferation demonstrated the pathogenic nature of the mutation. We therefore recommend screening the whole sequence of RET in MTC and pheochromocytoma patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Segregation analysis undertaken in the family demonstrated that it occurred "de novo", supporting its pathogenicity. Generally, RET defects associated with MEN2 and FMTC are typically gain of function, while deletions of part of the gene are mostly expected to cause loss of function; however, cases of RET deletions associated with MEN2 have been reported [40]. Moreover, Borganzone et al studied a similar somatic alteration of RET, p.Glu632_Leu633del (c.1894_1899delGAGCTG), and demonstrated that this in-frame deletion reduces the spacing between two Cysteine residues, causing ligand-independent constitutive dimerization and activation of RET.…”
Section: Families With Unclassified Variantsmentioning
confidence: 99%
“…Segregation analysis undertaken in the family demonstrated that it occurred "de novo", supporting its pathogenicity. Generally, RET defects associated with MEN2 and FMTC are typically gain of function, while deletions of part of the gene are mostly expected to cause loss of function; however, cases of RET deletions associated with MEN2 have been reported [40]. Moreover, Borganzone et al studied a similar somatic alteration of RET, p.Glu632_Leu633del (c.1894_1899delGAGCTG), and demonstrated that this in-frame deletion reduces the spacing between two Cysteine residues, causing ligand-independent constitutive dimerization and activation of RET.…”
Section: Families With Unclassified Variantsmentioning
confidence: 99%
“…Furthermore, the inclusion of just the hotspot exons of two PPGLs oncogenes, EPAS1 (exons 9 and 12) and RET (exons 8, 10, 11 and 13-16), instead of the entire coding region, was favoured for gene panels given the highly selective mutation distribution of these oncogenes 2,15,43,52 . However, these settings might need to be re-evaluated as the field evolves 53 .…”
Section: The Target Areamentioning
confidence: 99%
“…As the involvement of exon 7 in RET was not known when TGPs were designed, it was analyzed by SS. 36 DNA libraries were prepared according to the manufacturer's protocol, and samples were sequenced using the MiSeq platform (Illumina) with a paired-end mode using Composite tumor with ganglioneuroma, n Z 7: ID65, ID100, ID209, ID232, ID294, ID306, and ID435 Composite tumor with lymphoma, n Z 1: ID248 Presence of ACTH in the immunohistochemical study, n Z 3: ID108, ID304, and ID451…”
Section: Targeted Gene Panelsmentioning
confidence: 99%